Pembuatan Alat Peraga Hukum Ohm Untuk Materi Listrik Dinamis - Ahmad Hardyan Isnaini; Ahmad Ramdhani; Holis Angga Saputra; Rifki Rifaldy; Ansori Ansori (Indonesian, 2024)
Students' difficulty in understanding the concept of dynamic electricity, particularly Ohm's Law, presents a challenge in physics learning. This study aims to design and create a simple demonstration tool to visualize the relationship between voltage, current, and resistance in an electrical circuit. This study uses Thiagarajan's 4D development model, consisting of the stages of define, design, develop, and disseminate, although it only reached the development stage. The demonstration tool was designed using main components such as a resistor, voltmeter, ammeter, switch, and a 9-volt battery. Test results show that the tool functions according to the principles of Ohm's Law (V=IR), although there are slight variations due to the decrease in battery voltage during use. In testing resistor R1 (15 ohms), the input voltage was recorded at 5.28 volts with a current of 0.07 A, while for resistor R2 (39 ohms), the input voltage was recorded at 5.52 volts with a current of 0.03 A. The tool also provides a visual illustration through the changing light intensity of the lamp according to the electric current. This demonstration tool has been proven to help students understand the abstract concept of Ohm's Law visually and practically. With its simple design and affordable cost, this tool has great potential for use as a teaching aid in school laboratories, supporting active learning and enhancing students' understanding of dynamic electricity concepts.